2019
DOI: 10.1128/jvi.00064-19
|View full text |Cite
|
Sign up to set email alerts
|

EphA7 Functions as Receptor on BJAB Cells for Cell-to-Cell Transmission of the Kaposi's Sarcoma-Associated Herpesvirus and for Cell-Free Infection by the Related Rhesus Monkey Rhadinovirus

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) is the causative agent of Kaposi’s sarcoma and is associated with two B cell malignancies, primary effusion lymphoma (PEL) and the plasmablastic variant of multicentric Castleman’s disease. On several adherent cell types, EphA2 functions as a cellular receptor for the gH/gL glycoprotein complex of KSHV. KSHV gH/gL also has previously been found to interact weakly with other members of the Eph family of receptor tyrosine kinases (Ephs), and other A-type Ephs have b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…Thus, the mechanisms underlying KSHV targeting of plasma cells and other B lymphocyte lineages for infection remains to be established. Studies in lymphoma cell lines have identified ephrin receptors as critical factors in KSHV entry (Großkopf et al, 2019; Muniraju et al, 2019). Thus, our future studies in this area will concentrate on the role of other heparin sulfate proteoglycans and Ephrin family receptors in KSHV infection of tonsillar B lymphocyte lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the mechanisms underlying KSHV targeting of plasma cells and other B lymphocyte lineages for infection remains to be established. Studies in lymphoma cell lines have identified ephrin receptors as critical factors in KSHV entry (Großkopf et al, 2019; Muniraju et al, 2019). Thus, our future studies in this area will concentrate on the role of other heparin sulfate proteoglycans and Ephrin family receptors in KSHV infection of tonsillar B lymphocyte lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the mechanisms underlying KSHV targeting of plasma cells and other B lymphocyte lineages for infection remains to be established. Additional studies in lymphoma cell lines have identified Ephrin receptors as critical factors in KSHV entry [ 34 , 35 ]. Thus, our future studies in this area will examine Ephrin family receptors in KSHV infection of tonsillar B lymphocyte lineages.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies suggest that KSHV infection of epithelial cells is independent of αν-and β1-family integrin expression (TerBush et al, 2018), but requires HSPGs and either EphA2, EphA4, or EphA5 (Chakraborty et al, 2012a, Chandran, 2010, Chen et al, 2019, Damania and Cesarman, 2013, Hahn et al, 2012, TerBush et al, 2018. Interestingly, EphA7 has recently been found to be a receptor required for KSHV entry into B cells (Grosskopf et al, 2019). KSHV attachment to its host cells via HSPG and DC-SIGN is predominately mediated by gB and gpK8.1A (Fig.…”
Section: Kshv-driven Entry and Fusionmentioning
confidence: 99%